Deeper learning with QR codes and augmented reality : a scannable solution for your classroom - Burns, Monica, 1986- (Corwin, A SAGE Company, 2016)
Engaging, interactive learning-right in your students' hands! What if your students' mobile devices became an instructional asset rather than a distraction? Discover how free, scannable technology can enrich learning, while captivating students. Best of all, these technologies are easy to quickly implement within your classroom. Learn about QR codes and Augmented Reality (AR) Reach each student with new, hands-on learning opportunities Embrace the ACES Framework for teaching with scannable technologies: Access, Curate, Engage, and Share Promote self-directed learning and showcase students' cr.